1997
DOI: 10.1037/0893-3200.11.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Parenting, parent–child relationships, and sexual possibility situations among urban African American preadolescents: Preliminary findings and implications for HIV prevention.

Abstract: This article examines associations among parenting, parent-child relationships, and children's exposure to sexual possibility situations. African American families (N = 310) with preadotescent children were interviewed regarding parenting, parent-child relations, and demographic history. Children were interviewed privately about their exposure to sexual possibility situations. Results revealed marginal effects of child gender as well as effects of parent education and parent employment on children's exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…Previous work shows that children whose parents provide less monitoring and supervision are at higher risk for the early initiation of sexual intercourse [19 -22]. Presumably, children who are not monitored have more opportunities to spend time with other children, and greater time spent with other children as assessed in this study has been linked to early initiation of sexual intercourse [9,10].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Previous work shows that children whose parents provide less monitoring and supervision are at higher risk for the early initiation of sexual intercourse [19 -22]. Presumably, children who are not monitored have more opportunities to spend time with other children, and greater time spent with other children as assessed in this study has been linked to early initiation of sexual intercourse [9,10].…”
Section: Discussionmentioning
confidence: 69%
“…Paikoff demonstrated that such situations serve as opportunities among preadolescents to engage in sexual behaviors including sexual intercourse [9]. In a second study assessing factors associated with SPS, Paikoff et al [10] found that parenting support served as a protective factor in families where the mother had her first child as a teenager. They also found that parents' education and employment influenced the child's involvement in SPS.…”
mentioning
confidence: 97%
“…Parental control addresses who makes decisions in the family regarding key family issues. Paikoff et al (1997) did not find an association between parental control and situations of sexual possibility. However, Kapungu et al (in preparation), in a longitudinal study, found that boys of families with greater parental control were less likely to reach sexual debut in early adolescence.…”
Section: Sexual Possibility Situations and Peer Pressurementioning
confidence: 86%
“…Scores can range from 17 to 68, higher scores indicating low control. Paikoff et al (1997) found inter-item reliability was high (alpha = .76). The scale has been used previously with diverse adolescents (Holmbeck & O' Donnell, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Parental monitoring is related to delayed sexual initiation, decreases in other risk behaviors such as delinquency and drug use [2], and fewer opportunities for sexual activity to occur [24], i.e. fewer situations where teens gather in unsupervised, mixed-sex social groups and youth may witness sexual activity or engage in sexual behavior themselves [25]. Similarly, low parent monitoring and supervision are consistently linked to adolescent sexual activity [26] and problem behaviors among youth [27,28], including delinquency [29].…”
Section: Parental Monitoring and Supervisionmentioning
confidence: 99%